2016
DOI: 10.1039/c5nj01865j
|View full text |Cite
|
Sign up to set email alerts
|

V(iv), Fe(ii), Ni(ii) and Cu(ii) complexes bearing 2,2,2-tris(pyrazol-1-yl)ethyl methanesulfonate: application as catalysts for the cyclooctane oxidation

Abstract: New water-soluble scorpionate complexes were synthesized and applied as selective catalysts for cyclooctane oxidation in presence of basic or acid additives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 86 publications
0
24
0
Order By: Relevance
“…Their measured redox potentials in volts vs. saturated calomel electrode (V vs. SCE) and the eventual reversibility of the redox process, are indicated in Table 1. All authors found that C-homoscorpionate ligands are electrochemically inert in the potential range of −2.0 V to 2.0 V vs. SCE, at the used experimental conditions [46,[49][50][51][52][53][54]89,[91][92][93], thus no ligand centered oxidation or reduction has been reported to date.…”
Section: Electrochemical Properties Of C-scorpionate Metal Complexesmentioning
confidence: 99%
See 4 more Smart Citations
“…Their measured redox potentials in volts vs. saturated calomel electrode (V vs. SCE) and the eventual reversibility of the redox process, are indicated in Table 1. All authors found that C-homoscorpionate ligands are electrochemically inert in the potential range of −2.0 V to 2.0 V vs. SCE, at the used experimental conditions [46,[49][50][51][52][53][54]89,[91][92][93], thus no ligand centered oxidation or reduction has been reported to date.…”
Section: Electrochemical Properties Of C-scorpionate Metal Complexesmentioning
confidence: 99%
“…In addition, the tripodal functionalized coordination flexibility (e.g., N 3 -or N 2 O-coordination modes for sulfonated derivatives, Figure 5d) involving the functionalized methine carbon [7,8,14,45,49,50] is also tailored by such co-ligands, an important pre-requisite for their catalytic activity.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations